2019
DOI: 10.37358/rc.19.2.6964
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Effects of Aluminium on Plant Growth in Three Culture Plants Species

Abstract: Aluminium toxicity is one of the major factors that limit plant growth and development in many acid soils, by multiple, and still poorly understood mechanisms. In this paper, the aluminium content determinations were done through atomic absorption spectrometry method, on seedlings of three culture plants, Helianthus annuus L. (sunflower), Sinapis alba L. (white mustard) and Triticum aestivum L. (wheat), grown in hydroponic conditions with different aluminium concentrations (50, 100 and 250 mg/kg) expose. AAS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While flavonoid content in Pyracantha was less studied, some data are available from related genera, like Cotoneaster sp. The literature mention that Cotoneaster horizontalis would contain 6800 mg/kg [17], while Cotoneaster multiflorus fruit contain up to 53700 mg/kg DW flavonoids (amount highly dependent on solvents used) [18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…While flavonoid content in Pyracantha was less studied, some data are available from related genera, like Cotoneaster sp. The literature mention that Cotoneaster horizontalis would contain 6800 mg/kg [17], while Cotoneaster multiflorus fruit contain up to 53700 mg/kg DW flavonoids (amount highly dependent on solvents used) [18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…A study on germination and development of mustard seeds in Cr-polluted soil indicated that white mustard is tolerant to high Cr levels and has hyper accumulative abilities [13]. Another study that looked at the effect of aluminum (Al) whose toxicity can inhibit mustard germination and development in acidic soils indicated that it does not accumulate in plant matter, but productivity may be impaired [14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is concerned with several diseases as Parkinson and Alzheimer's [4,5], bone softening, renal failure and anaemia [6]. Al presents in soils naturally in the form of minerals as, alumino-silicates (kaolin, feldspars and micas), hydroxides and oxides [7]. Foods and water are the most important sources for Al exposure.…”
Section: Introductionmentioning
confidence: 99%